Fertilization differences alter the diversity and function of tea plant rhizosphere soil microbial communities, thus affecting tea plant growth - Zhang, Qi; Guo, Songhan; Wang, Yulin; Liao, Yankun; Jia, Xiaoli; Zhu, Bitong; Weng, Qiqi; Wang, Haibin; Ye, Jianghua (Frontiers in Microbiology, 2025)
IntroductionFertilization is one of the main agronomic measures in tea plantation management, but the effects of different fertilization patterns on the structure, function, and growth of tea plant rhizosphere soil microbial communities are still unclear.MethodsThis study compared the effects of three fertilization treatments: 100% chemical fertilizer (CF), 50% chemical fertilizer + 50% organic fertilizer (COF), and 100% organic fertilizer (OF) on tea plant growth and rhizosphere soil microorganisms. Plant growth indicators were measured, and soil microbial communities were analyzed via high-throughput sequencing of 16S rDNA and ITS regions. Microbial functions were predicted using FAPROTAX and FUNGuild.ResultsThe COF treatment resulted in the most significant promotion of tea plant growth, with the highest chlorophyll content (30.47 SPAD), leaf area (18.76 cm2), and hundred-bud weight (18.22 g). Soil microbial analysis revealed that while COF treatment significantly increased microbial biomass carbon (151.05 mg/kg) and phosphorus (105.56 mg/kg), CF treatment was more conducive to accumulating microbial biomass nitrogen (130.47 mg/kg). High-throughput sequencing indicated that COF treatment exerted the strongest impact on bacterial community structure, while OF treatment enhanced the migration rate and α diversity of both bacteria and fungi. Different fertilization treatments primarily altered the abundance of key microorganisms Opitutus and Coccocarpia, thereby influencing microbial fermentation and lichenized functions. Specifically, COF increased the abundance of Coccocarpia and reduced the abundance of Opitutus, thereby promoting soil lichenized functions while reducing fermentation functions.DiscussionThe synergistic effect of combined chemical and organic fertilization enhances lichenized function and suppresses fermentation, which in turn improves the accumulation of soil microbial biomass carbon, nitrogen, and phosphorus, ultimately fostering tea plant growth. These findings suggest that the COF fertilization strategy can be further optimized and provide a theoretical basis for scientific fertilization management in tea plantations.